The Geometrinae of Ethiopia II: Tribus Hemistolini, genus Prasinocyma(Lepidoptera: Geometridae, Geometrinae) - Hausmann, Axel; Sciarretta, Andrea; Parisi, Francesco (Zootaxa, 2016)
In this paper we present a checklist and integrative revision for the genus Prasinocyma (Geometridae, Geometrinae, Hemistolini). With this contribution the checklist for the genus Prasinocyma in Ethiopia increases from eight to 40 species. Nineteen species and five subspecies are described as new for the science: Prasinocyma pedicata aethiopica subsp. n., Prasinocyma angolica pseudopedicata subsp. n., Prasinocyma bongaensis sp. n., Prasinocyma getachewi sp. n., Prasinocyma baumgaertneri sp. n., Prasinocyma robusta sp. n., Prasinocyma shoa yabellensis subsp. n., Prasinocyma amharensis sp. n., Prasinocyma magica sp. n., Prasinocyma batesi distans subsp. n., Prasinocyma monikae sp. n., Prasinocyma fusca sp. n., Prasinocyma leveneorum sp. n., Prasinocyma aquamarina sp. n., Prasinocyma beryllaria sp. n., Prasinocyma lutulenta sp. n., Prasinocyma septentrionalis sp. n., Prasinocyma fallax sp. n., Prasinocyma trematerrai sp. n., Prasinocyma trematerrai simienensis subsp. n., Prasinocyma angulifera sp. n., Prasinocyma stefani sp. n., Prasinocyma gemmifera sp. n., Prasinocyma discipuncta sp. n. Prasinocyma thiaucourti Herbulot, 1993 is downgraded from species rank to subspecies of P. immaculata (Thunberg, 1784) (stat. n.). Prasinocyma unipuncta Warren, 1897 is downgraded from species rank to synonymy of P. immaculata (Thunberg, 1784) (syn. n.). Prasinocyma nereis Townsend, 1952 (comb.n.) is transferred from genus Eretmopus to Prasinocyma. Thalassodes camerunalta Herbulot, 1986 (comb.n.) is transferred from genus Thalassodes to Prasinocyma. Thalassodini (syn.n.) are downgraded to synonymy of Hemistolini, here.